Partisipasi Civil Society dalam Penanggulangan Sampah di Lokasi Pariwisata Kabupaten Lampung Barat - Apandi; Prihantika, Ita; Atika, Dewie Brima; Meutia, Intan Fitri (Wacana Publik, 2023)
Pesisir Barat Regency produces approximately 1.2 tonnes of waste every day. This condition makes it imperative for the West Pesisir District Government to take waste management more seriously and of course requires the support of many parties. One of the communities actively involved in waste management is Krui Kecah Ko. This research uses a qualitative method. Data collection was done through interviews, observation and documentation in the research. Then compile the theory and data. Community participation in waste management at Krui tourism site in West Lampung Regency was initiated by a youth-led community. The concern and attention by this young group is an excellent social capital in changing the behaviour and culture of the community and tourists in disposing of waste. The movement is combined with the use of digital media (both news coverage and social media campaigns) so as to encourage Gen Z participation to care and be involved in handling waste in tourist areas.